A basketball is shot from a height of 6 feet with an initial upward velocity of 20 feet per second. The height of the basketball can be represented by the equation

h = -16t^2 + 20t + 64 where t = time after the shot in seconds and h = the height in feet. When will the basketball hit the ground?

11 answers

To determine when the basketball hits the ground, we need to find the time \( t \) when the height \( h \) is zero. The height equation is given by:

\[ h = -16t^2 + 20t + 64 \]

We set \( h \) equal to zero and solve for \( t \):

\[ 0 = -16t^2 + 20t + 64 \]

This is a quadratic equation in the standard form \( at^2 + bt + c = 0 \), where:

  • \( a = -16 \)
  • \( b = 20 \)
  • \( c = 64 \)

We can solve this using the quadratic formula:

\[ t = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]

Substituting the values of \( a \), \( b \), and \( c \):

\[ t = \frac{-20 \pm \sqrt{20^2 - 4(-16)(64)}}{2(-16)} \]

Calculating the discriminant:

\[ 20^2 = 400 \] \[ 4(-16)(64) = -4096 \implies \text{Since it's negative, we actually do: } 4(16)(64) = 4096 \] \[ b^2 - 4ac = 400 + 4096 = 4496 \]

Now we plug this back into the formula:

\[ t = \frac{-20 \pm \sqrt{4496}}{-32} \]

Calculating \( \sqrt{4496} \):

\[ \sqrt{4496} \approx 67.07 \]

Now plug this back in:

\[ t = \frac{-20 \pm 67.07}{-32} \]

Calculating the two potential times:

  1. Using the positive root: \[ t = \frac{-20 + 67.07}{-32} = \frac{47.07}{-32} \approx -1.47 \text{ (Not physically relevant, as time cannot be negative)} \]

  2. Using the negative root: \[ t = \frac{-20 - 67.07}{-32} = \frac{-87.07}{-32} \approx 2.72 \]

Thus, the basketball will hit the ground approximately at:

\[ \boxed{2.72} \text{ seconds} \]

Determine whether
3/4 is the solution to the following quadratic equation 8x^2 – 6x - 3 = 0. Show your work.

To determine whether \( \frac{3}{4} \) is a solution to the quadratic equation

\[ 8x^2 - 6x - 3 = 0, \]

we will substitute \( x = \frac{3}{4} \) into the equation and check if the resulting expression equals zero.

  1. Substitute \( x = \frac{3}{4} \) into the equation:

\[ 8\left(\frac{3}{4}\right)^2 - 6\left(\frac{3}{4}\right) - 3 \]

  1. Calculate \( \left(\frac{3}{4}\right)^2 \):

\[ \left(\frac{3}{4}\right)^2 = \frac{9}{16} \]

  1. Now substitute back into the equation:

\[ 8 \left(\frac{9}{16}\right) - 6 \left(\frac{3}{4}\right) - 3 \]

  1. Simplify \( 8 \left(\frac{9}{16}\right) \):

\[ 8 \cdot \frac{9}{16} = \frac{72}{16} = \frac{9}{2} \]

  1. Simplify \( -6 \left(\frac{3}{4}\right) \):

\[ -6 \cdot \frac{3}{4} = -\frac{18}{4} = -\frac{9}{2} \]

  1. Substituting these values back:

\[ \frac{9}{2} - \frac{9}{2} - 3 \]

  1. Combine the terms:

\[ 0 - 3 = -3 \]

  1. Result:

Since

\[ 8\left(\frac{3}{4}\right)^2 - 6\left(\frac{3}{4}\right) - 3 = -3 \neq 0, \]

we conclude that \( \frac{3}{4} \) is not a solution to the equation \( 8x^2 - 6x - 3 = 0 \).

Therefore, \( \frac{3}{4} \) is not a solution.

Determine whether -1 is a solution to the following quadratic equation
4x^2 + 4x + 1 = 0. Show your work.

To determine whether \( -1 \) is a solution to the quadratic equation

\[ 4x^2 + 4x + 1 = 0, \]

we will substitute \( x = -1 \) into the equation and check if the result is equal to zero.

  1. Substitute \( x = -1 \) into the equation:

\[ 4(-1)^2 + 4(-1) + 1 \]

  1. Calculate \( (-1)^2 \):

\[ (-1)^2 = 1 \]

  1. Now substitute back into the equation:

\[ 4(1) + 4(-1) + 1 \]

  1. Simplify each term:

\[ 4(1) = 4, \] \[ 4(-1) = -4, \]

So we have:

\[ 4 - 4 + 1 \]

  1. Combine the terms:

\[ 4 - 4 + 1 = 0 + 1 = 1 \]

  1. Result:

Since

\[ 4(-1)^2 + 4(-1) + 1 = 1 \neq 0, \]

we conclude that \( -1 \) is not a solution to the equation \( 4x^2 + 4x + 1 = 0 \).

Therefore, \( -1 \) is not a solution.

Write the following equation in vertex form
y = x2 + 6x - 1.

To convert the quadratic equation \( y = x^2 + 6x - 1 \) into vertex form, we will complete the square. The vertex form of a quadratic equation is given by:

\[ y = a(x - h)^2 + k \]

where \((h, k)\) is the vertex of the parabola.

Step 1: Start with the original equation

\[ y = x^2 + 6x - 1 \]

Step 2: Group the quadratic and linear terms and prepare to complete the square

Focus on the \( x^2 + 6x \) part:

\[ y = (x^2 + 6x) - 1 \]

Step 3: Complete the square

To complete the square for \( x^2 + 6x \), we take half of the coefficient of \( x \) (which is \( 6 \)), square it, and add/subtract it. Half of \( 6 \) is \( 3 \), and squaring it gives \( 9 \).

Add and subtract \( 9 \):

\[ y = (x^2 + 6x + 9 - 9) - 1 \]

Simplifying this gives:

\[ y = ((x + 3)^2 - 9) - 1 \]

Step 4: Combine the constants

Now simplify:

\[ y = (x + 3)^2 - 10 \]

Final Result

Thus, the vertex form of the equation is:

\[ y = (x + 3)^2 - 10 \]

The vertex of this equation is at the point \( (-3, -10) \).

Identify the vertex of
y =-5(x - 8)^2+ 12

The equation you provided is already in vertex form, which is given by:

\[ y = a(x - h)^2 + k \]

In this format, the vertex of the parabola is given by the point \((h, k)\).

For the equation \( y = -5(x - 8)^2 + 12 \):

  • \( h = 8 \)
  • \( k = 12 \)

Therefore, the vertex of the equation is:

\[ \boxed{(8, 12)} \]

Identify the vertex and axis of symmetry of the parabola

on the left side bottom to top of the graph it goes from -5 to 15 and the left side to right side 0 to 15, there's an arch going from -5 going upwards 15 and downwards 15 again

To identify the vertex and axis of symmetry of a parabola from your description, let's break down the information you've provided:

  1. Vertex:

    • Since you mentioned that the graph goes from -5 going upwards to 15 and then downwards again, it sounds like the vertex is the highest point of the parabola. From your description, it seems that the vertex of the parabola is at the top of the arch. Therefore, this point would be at \( (x, y) = (0, 15) \).
  2. Axis of Symmetry:

    • The axis of symmetry is a vertical line that passes through the vertex of the parabola. For a parabola that opens downwards and has its vertex at \( (0, 15) \), the axis of symmetry is \( x = 0 \).

Conclusion:

  • Vertex: \((0, 15)\)
  • Axis of Symmetry: \(x = 0\)

If the vertex does not match your description exactly or if the graph has other specific characteristics, please provide more details to refine this analysis further!